Application of Hedonic Pricing Model and Geographic Information System on Property Valuation in Yogyakarta - Amalia, Nurisqi; Yuniyarti, Nur Aini; Prativi, Fatima Putri (Universitas Ahmad Dahlan, Yogyakarta, 2024)
This study aims to: 1) identify the differences in housing choices between Generation Z (students) and the previous generation (parents or guardians); 2) determine the factors influencing housing purchase decisions; and 3) map the areas of interest for Universitas Gadjah Mada (UGM) students based on price. The research employs a combination of the Hedonic Pricing Model (HPM) and Geographic Information System (GIS), a method that remains limited in the field of property research. The findings reveal that significant factors affecting property prices are building area and location, with the majority of UGM students choosing to reside in Ngaglik District, Sleman Regency. Sleman Regency is also the predominant area where UGM students purchase housing in Yogyakarta. Key attributes influencing UGM students' housing decisions include a safe neighbourhood, residential environment, and distance from waste centers. This research contributes valuable information to property appraisers regarding property price distribution in Yogyakarta and its influencing factors, and provides crucial insights for effective decision-making and policy implementation in regional economic development planning, especially in less popular areas.